The Usage of System Dynamics in Organizational Interventions A Participative Modeling Approach Supporting Change Management Efforts - Snabe, Birgitte; SpringerLink (Online service) (Wiesbaden : DUV, 2007)
Internationalization and globalization are major incentives for companies to change their organizational structures and processes fundamentally. To master the associated problems, especially in the area of human resource management, sound and well planned procedures are indispensable and have to take into account both structural and dynamic aspects. Birgitte Snabe analyzes how system dynamics modeling can be used in learning processes that focus on the transfer of the insights and reasoning behind a strategy forming process. In a second step, she shows how it can support the refining of implementation plans. A case study in action research tradition completes the theoretical discussions. Its subject is the building up of a large international company$1 (Bs R&D resources in low-cost countries.s
Organizational Intervention Skills as Corporate Competence -- Conceptual Foundation for the Usage of System Dynamics -- A Case Study Using Participative System Dynamics Modeling in the Implementation of a Sensitive Change Project -- The Usage and Utility of Participative Modeling in Change Management -- Targeted Participative Modeling in Change Management.
Keywords: Business; Management; Organization; Planning; Business and Management; Organization; Management; Electronic books